2016
DOI: 10.1208/s12248-016-9962-6
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Opportunities with Non-CYP Enzymes Aldehyde Oxidase, Carboxylesterase, and UDP-Glucuronosyltransferase: Focus on Reaction Phenotyping and Prediction of Human Clearance

Abstract: Over the years, significant progress has been made in reducing metabolic instability due to cytochrome P450-mediated oxidation. High throughput metabolic stability screening has enabled advancement of compounds with little to no oxidative metabolism. Furthermore, high lipophilicity and low aqueous solubility of presently pursued chemotypes reduces the probability of renal excretion. As such, these low microsomal turnover compounds are often substrates for non CYP-mediated metabolism. UGTs, esterases and aldehy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 112 publications
2
66
0
Order By: Relevance
“…Interestingly, the conventional scaling showed better performance for the mainly CYP-metabolized reference compounds in the long-term co-culture system HepatoPac as compared to the direct scaling approach. The better performance of direct scaling for the in vivo clearance prediction of Roche compounds might be due to the involvement of non-CYP enzymes and transporters, which gives rise to larger underprediction compared to CYP-metabolized reference compounds (42,43). These results demonstrated that the performance of the scaling approach was dependent on the applied in vitro liver model, the chemical space of the selected compound set, i.e., their physicochemical properties, such as plasma protein binding, and the involved clearance routes.…”
Section: Ivive Of In Vitro Clearance Assessmentsmentioning
confidence: 99%
“…Interestingly, the conventional scaling showed better performance for the mainly CYP-metabolized reference compounds in the long-term co-culture system HepatoPac as compared to the direct scaling approach. The better performance of direct scaling for the in vivo clearance prediction of Roche compounds might be due to the involvement of non-CYP enzymes and transporters, which gives rise to larger underprediction compared to CYP-metabolized reference compounds (42,43). These results demonstrated that the performance of the scaling approach was dependent on the applied in vitro liver model, the chemical space of the selected compound set, i.e., their physicochemical properties, such as plasma protein binding, and the involved clearance routes.…”
Section: Ivive Of In Vitro Clearance Assessmentsmentioning
confidence: 99%
“…Successful mitigation of CYP450 metabolic liabilities during drug development has increased the importance of non‐CYP450 enzyme contributions to drug metabolism. However, evaluation of non‐CYP450 mediated xenobiotic metabolism continues to pose research, development, and regulatory challenges . Standardized in vitro models to assess conjugating enzyme contributions to xenobiotic clearance and approaches to predict clinical consequences are evolving.…”
Section: Discussionmentioning
confidence: 99%
“…Of the non‐CYP450 enzymes that contribute to xenobiotic metabolism, UGTs are the most important in terms of abundance in hepatic and extrahepatic tissues as well as in the wide range of xenobiotics including many drugs and endobiotics they metabolize. Drug–drug interactions mediated via UGT induction are inherently difficult to predict from in vitro data . LC‐MS/MS approaches to directly quantify UGT protein content within in vitro systems and human tissues have enhanced in vitro–‐in vivo extrapolation of UGT mediated metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, other analytical difficulties limit the amount of useful kinetic information available for UGTs and makes them difficult to model . In particular, the active sites of UGTs are internally oriented (facing the lumen) in liver microsomes .…”
Section: Metabolic Predictionsmentioning
confidence: 99%
“…Hence esters that are readily cleaved in plants, fungi or insects are also likely to be cleaved in the human gastrointestinal tract or liver. 28 There is rarely much point in trying to build a QSAR model for such a reaction. The better approach to pro-pesticides is to identify ethyl and other short-chain, unbranched esters 29 and 'cleave' them in silico before applying QSAR models.…”
Section: Hydrolytic and Conjugative Metabolismmentioning
confidence: 99%